2022
DOI: 10.12688/wellcomeopenres.17202.3
|View full text |Cite
|
Sign up to set email alerts
|

Validation and clinical application of a method to quantify efavirenz in cervicovaginal secretions from flocked swabs using liquid chromatography tandem mass spectrometry

Abstract: Background : A liquid chromatography tandem mass spectrometry method to quantify drugs in dried cervicovaginal secretions from flocked swabs was developed and validated using the antiretroviral efavirenz as an example. Methods: Cervicovaginal swabs (CVS) were prepared by submerging flocked swabs in efavirenz-spiked plasma matrix. Time to full saturation, weight uniformity, recovery and room temperature stability were evaluated. Chromatographic separation was on a reverse-phase C18 column by gradient elution us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The understanding of antiretroviral pharmacokinetics in the female genital tract (FGT) is of growing interest in the HIV prevention field because of its importance in designing more effective therapeutic options to reduce serodiscordant and mother-to-child HIV transmission [1]. Although a number of clinical studies that focus on quantifying antiretroviral drugs in the FGT have been reported in the literature [2][3][4][5][6]. ARV characterization in this compartment has not yet been well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of antiretroviral pharmacokinetics in the female genital tract (FGT) is of growing interest in the HIV prevention field because of its importance in designing more effective therapeutic options to reduce serodiscordant and mother-to-child HIV transmission [1]. Although a number of clinical studies that focus on quantifying antiretroviral drugs in the FGT have been reported in the literature [2][3][4][5][6]. ARV characterization in this compartment has not yet been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent these challenges, , cervicovaginal fluids (CVF are used as an acceptable surrogate for vaginal tissue concentrations of ARVs [20]. In our laboratory, we recently validated a minimally invasive LC-MS/MS method to quantify the HIV drug efavirenz in cervicovaginal fluid collected on flock swabs [6], which improved our ability to conduct intensive clinical pharmacokinetic studies with CVF.…”
Section: Introductionmentioning
confidence: 99%